The simplification of
10+4÷2-3×2+4÷2×2
Answers
Answered by
1
Answered by
0
Simplification
Explanation:
10 + 4 ÷ 2 - 3 × 2 + 4 ÷ 2 × 2
We will use the rule of BODMAS for this:
In the above, there is no brackets so we'll solve division first.
= 10 + 4 ÷ 2 - 3 × 2 + 4 ÷ 2 × 2
= 10 + 2 - 3 × 2 + 2 × 2
Now, we will solve multiplication.
= 10 + 2 - 3 × 2 + 2 × 2
= 10 + 2 - 6 + 4
Now, we will solve addition.
= 10 + 2 - 6 + 4
= 12 - 10
Now, finally we will subtract.
= 12 - 10
= 2
So, the answer is 2.
Similar questions